Artificial Supramolecular Pumps Powered by Light. Issue 43 (27th June 2021) - Corra, Stefano; Casimiro, Lorenzo; Baroncini, Massimo; Groppi, Jessica; La Rosa, Marcello; Tranfić Bakić, Marina; Silvi, Serena; Credi, Alberto
Abstract: Invited for the cover of this issue is Alberto Credi and co‐workers at the University of Bologna and National Research Council, Bologna, Italy. The image represents the photostationary non‐equilibrium operation of supramolecular pumps as a hydraulic circuit in which water flows between reservoirs. Read the full text of the article at 10.1002/chem.202101163 . Abstract : " We present an improved version of a rotaxane‐based system in which unidirectional threading and dethreading of the molecular components can be carried out repeatedly under stationary optical excitation in solution. By performing the photoreaction in the probe of the NMR spectrometer, we were able to investigate the photoinduced non‐equilibrium behavior of the system, and in particular distinguish between kinetically trapped and stationary dissipative regimes ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 11076 ff. (DOI: 10.1002/chem.202101163 ).